2019
DOI: 10.3390/genes10090675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Type, and Molecular Spectrum of NF1 Mutations in Patients with Neurofibromatosis Type 1 and Congenital Heart Disease

Abstract: The aim of this study was to assess the prevalence and type of congenital heart disease (CHD) and the associated mutation spectrum in a large series of patients with neurofibromatosis type 1 (NF1), and correlate the mutation type with the presence and subgroups of cardiac defects. The study cohort included 493 individuals with molecularly confirmed diagnosis of NF1 for whom cardiac evaluation data were available. CHD was reported in 62/493 (12.6%) patients. Among these patients, 23/62 (37.1%) had pulmonary val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…Cardiovascular malformations have been reported in many patients with NF1 [10,11], but overall frequency of these findings in NF1-deleted patients had never been evaluated before. Pulmonic stenosis is the most frequently reported congenital heart disease in NF1 and is almost always found in association with Noonan-like features [20], as it is the case in our NF1-deleted group (n = 2/2 patients with pulmonic stenosis and dysmorphic features). Altogether, cardiovascular abnormalities were frequent in our group (23%, 15/64) and included hypertension (n = 7), pulmonic stenosis (n = 2), aortic stenosis (n = 1), extra-dural hematoma (n = 1), patent ductus arteriosus (n = 1), septal hypertrophy (n = 1), aberrant vessel in ascending aorta (n = 1), and occlusion of the left internal carotid artery (n = 1).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Cardiovascular malformations have been reported in many patients with NF1 [10,11], but overall frequency of these findings in NF1-deleted patients had never been evaluated before. Pulmonic stenosis is the most frequently reported congenital heart disease in NF1 and is almost always found in association with Noonan-like features [20], as it is the case in our NF1-deleted group (n = 2/2 patients with pulmonic stenosis and dysmorphic features). Altogether, cardiovascular abnormalities were frequent in our group (23%, 15/64) and included hypertension (n = 7), pulmonic stenosis (n = 2), aortic stenosis (n = 1), extra-dural hematoma (n = 1), patent ductus arteriosus (n = 1), septal hypertrophy (n = 1), aberrant vessel in ascending aorta (n = 1), and occlusion of the left internal carotid artery (n = 1).…”
Section: Discussionsupporting
confidence: 70%
“…Heritability studies have suggested the existence of a genetic component of the variable expressivity [17][18][19]. A large spectrum of pathogenic variations has been reported in the NF1 gene [2,20,21], with 2783 unique variants reported in the Global Variome shared Leiden Open Variation Database (LOVD) on 19 February 2021. However, genetic studies have generally failed to establish clear-cut genotype-phenotype correlations according to the type of NF1 pathogenic variant [2,22].…”
Section: Introductionmentioning
confidence: 99%
“…As to NF1-related multisystem features, SNVs localized to the 5′ tertile of NF1 and affecting residues 1-909 (including CSRD) have been associated with a higher incidence of short stature, especially loss-of-function variants [ 47 ]. A higher prevalence of non-truncating intragenic variants was observed in patients with congenital heart defects (CHD), with a two- and six-fold higher risk of developing CHD and PS, respectively [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 90%–95% of cases, the disease is caused by an intragenic mutation (frameshift, nonsense, splice site mutation, and copy number variation) while the remaining 5%–10% by long deletions (whole-gene deletion WDG). [ 6 ] De novo mutations of the NF-1 gene represent about 50% of the cases, explaining the presence of patients with a familiar negative history.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent pathologies described are mitral valve anomalies, interatrial septal abnormalities (ostium secundum and septal aneurysm), pulmonary valve stenosis, cardiomyopathy, and aortic valve insufficiency. [ 3 6 10 ]…”
Section: Introductionmentioning
confidence: 99%